Optimization of ultrasonic-assisted extraction of anthocyanins, flavonoids and their antioxidant activity from Doi Saket purple rice (Oryza sativa L.) - Rajchasom, Sureewan; Sombatnan, Pornsawan; Tanongkankit, Yardfon; Narkprasom, Nukrob (Agriculture and Natural Resources, 2026)
Importance of the work: Doi Saket purple rice (Oryza sativa L.) is rich in anthocyanins, which are found primarily in the rice grain. However, anthocyanins are sensitive to heat, pH, light, solvents, enzymes and oxidative stress compounds. Systematic evaluation and optimization of the extraction parameters and conditions is essential to maximize the yield of bioactive compounds through ultrasonic-assisted extraction. Objective: To investigate the optimization of various factors influencing ultrasonic-assisted extraction (UAE) of the total anthocyanin content (TAC), total flavonoid content (TFC) and hydrogen peroxide (H2O2) scavenging activity from Doi Saket purple rice using response surface methodology (RSM). Materials and Methods: The Doi Saket purple rice was extracted using UAE and the optimum conditions were determined based on RSM. A Box-Behnken design was used to plan the experimental runs, resulting in 15 experimental conditions. Three factors, each at three levels were studied: solid-to-liquid ratio (1:1−1:3 weight per volume, w/v; X1), extraction time (20-60 min; X2) and extraction temperature (60-80°C; X3). Results: The optimal conditions for the UAE of TAC, TFC and H2O2 scavenging activity of Doi Saket purple rice were a solid-to-liquid ratio of 1:2 w/v, an extraction time of 40 min and an extraction temperature of 70°C. Under these conditions, the highest predicted values for TAC, TFC and H2O2 scavenging activity were 131.83 mg/g, 38.62 mg of quercetin equivalent/g rice (mg QE/g) and 83.75%, respectively. The experimental values mean (± SD) of the extracts obtained under optimal conditions were as follows: TAC, 112.77 ± 2.34 mg/g; TFC, 39.26 ± 0.35 mg QE/g and H2O2 scavenging activity, 75.06 ± 1.26%. Main finding: The independent variables (solid-to-liquid ratio, extraction time and extraction temperature) were systematically identified and optimized to maximize the extraction yields of TAC, TFC and H2O2 scavenging activity from Doi Saket purple rice.